2011
DOI: 10.1097/aln.0b013e318210f9e3
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative Tranexamic Acid Reduces Blood Transfusion in Children Undergoing Craniosynostosis Surgery

Abstract: Background: Surgical correction of craniosynostosis in children is associated with substantial intraoperative bleeding. Tranexamic acid (TXA) decreases intraoperative blood loss during cardiac or orthopedic surgery in children. We hypothesized that intraoperative TXA would reduce blood transfusion relative to placebo in patients pretreated with erythropoietin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
192
2
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 212 publications
(206 citation statements)
references
References 35 publications
9
192
2
3
Order By: Relevance
“…Tranexamic acid has been used to decrease intraoperative blood loss during cardiac surgery. In a randomized double-blind study 33 published in 2011, patients undergoing surgical correction of craniosynostosis who were treated with erythropoietin before surgery and with tranexamic acid during the operation sustained significantly lower volumes of blood loss and received less transfused blood than did the control patients.…”
Section: Intraoperative Periodmentioning
confidence: 99%
See 2 more Smart Citations
“…Tranexamic acid has been used to decrease intraoperative blood loss during cardiac surgery. In a randomized double-blind study 33 published in 2011, patients undergoing surgical correction of craniosynostosis who were treated with erythropoietin before surgery and with tranexamic acid during the operation sustained significantly lower volumes of blood loss and received less transfused blood than did the control patients.…”
Section: Intraoperative Periodmentioning
confidence: 99%
“…Transfusion requirements can be 15% to 90% of the patient's circulating red cell volume. 33,34 Numerous techniques intended to reduce intraoperative blood loss during craniosynostosis surgery have been studied, including use of autologous blood obtained before surgery, short-term nomovolemic hemodilution, and intraoperative blood salvage. 12,15 Tranexamic acid is a synthetic antifibrinolytic drug that competitively decreases the activation of plasminogen to plasmin and suppresses fibrinolysis by inhibiting plasminogen and the binding of plasmin to fibrin.…”
Section: Intraoperative Periodmentioning
confidence: 99%
See 1 more Smart Citation
“…Preoperatively, autologous donations, EPO administration, new upper age limits for surgical correction, and surgical patient screening have been attempted. 10,17,18,29 Changes in anesthetic management have also been attempted to decrease perioperative transfusion rates, including acute normovolemic hemodilution (ANH), acceptance of lower hemoglobin levels, the use of autologous blood cell recycling, 14 induced hypotension, infusion of antifibrinolytic agents (amicar, tranexamic acid, aprotinin), 4,22 and factor administration (activated factor VIIa, prothrombin complex concentrate [PCC]).…”
Section: Discussionmentioning
confidence: 99%
“…Craniosynostosis is not an uncommon pediatric disease requiring early surgical intervention and is associated with considerable blood loss [53]. There are two RCTs of TXA vs control in craniosynostosis surgery [54,55]: Goobie et al showed significant decrease in blood loss of 54 mL kg-1 and decreased volume of blood transfused by 23 mL kg -1 ; Dadure et al [55] found a decrease in transfusion requirement by 85% (11 to 1.6 mL kg -1 ) intraoperatively and by 57% (16.6 to 7.2 mL kg -1 ) postoperatively. Moreover, Goobie et al [44] describes a dose regimen for craniosynostosis using a twocompartment model, suggesting a 10 mg kg -1 loading TXA followed by a 5 mg kg -1 h -1 infusion to produce a threshold plasma concentration of 16 µg mL -1 .…”
Section: Ppediatric Cardiac and Non-cardiac Surgerymentioning
confidence: 99%